Etomoxir Sodium Salt Promotes Imidazole Ketone Erastin-Induced Myeloid-Derived Suppressor Cell Ferroptosis and Enhances Cancer Therapy - Nada Mohamady Farouk Abdalsalam; Zihao Liang; Hafiza Kashaf Tariq; Abdulrahman Ibrahim; Rong Li; Xiaochun Wan; Dehong Yan (Biology)
Although ferroptosis inducers trigger ferroptotic tumor cells and immune cells in the tumor microenvironment (TME), imidazole ketone erastin (IKE)’s induction of ferroptosis shows no effect on tumor growth in immunocompetent tumor-bearing mice due to the presence of myeloid-derived suppressor cells (MDSCs). Treatment of the carnitine palmitoyltransferase 1a (CPT1A)-specific inhibitor decreases the immunosuppressive function of MDSCs and enhances ferroptotic inducer-initiated tumor cell ferroptosis. However, whether blocking CPT1A could enhance IKE-induced MDSC ferroptosis and thereby inhibit tumor growth is still unclear. Here, we report that a CPT1A-specific inhibitor, etomoxir sodium salt (Eto), and IKE combined treatment increased MDSC ferroptosis. Interestingly, the combination treatment of Eto and IKE blocked MDSCs’ immunosuppressive function and accumulation by downregulating the expression of SLC7A11, GPX4, and ARG1 while promoting T-cell proliferation and infiltration into tumor tissues to enhance cancer therapy. These data provide a rationale for the combination therapy of a specific CPT1A inhibitor, Eto, with IKE in clinical settings.